Frequency Response Characteristics of Rogowski Coil with Active Integrator for Lightning Measurement - Busayapol Paophan; Anantawat Kunakorn; Peerawut Yutthagowith; Kazuo Yamamoto (My University, 2020)
This paper presents frequency response characteristics of a Rogowski coil which is developed with an active integrator. Experiments are performed in a laboratory with a frequency function generator as a source. The frequency responses of the Rogowski coil and the integrator are recorded with both magnitude and phase in order to verify the capability in measuring lightning current waveshapes. For availability in lightning current measurement in the electrical system, the developed Rogowski coil is specifically designed as a clamp on device. The standard lightning current waveshape of the first positive impulse (10/350μs) is simulated to investigate the measuring system. It is found that the frequency bandwidth of the Rogowski coil with the integrator developed in this paper is proper in lightning current measurement.
Keywords: Magneto-Optical Properties and Applications